Recipient Tregs: Can They Be Exploited for Successful Hematopoietic Stem Cell Transplant Outcomes? - Copsel, Sabrina N.; Wolf, Dietlinde; Pfeiffer, Brent; Barreras, Henry; Perez, Victor L.; Levy, Robert B. (Frontiers in Immunology, 2022)
Human and mouse CD4+FoxP3+ T cells (Tregs) comprise non-redundant regulatory compartments which maintain self-tolerance and have been found to be of potential therapeutic usefulness in autoimmune disorders and transplants including allogeneic hematopoietic stem cell transplantation (allo-HSCT). There is substantial literature interrogating the application of donor derived Tregs for the prevention of graft versus host disease (GVHD). This Mini-Review will focus on the recipient’s Tregs which persist post-transplant. Although treatment in patients with low dose IL-2 months post-HSCT are encouraging, manipulating Tregs in recipients early post-transplant is challenging, in part likely an indirect consequence of damage to the microenvironment required to support Treg expansion of which little is understood. This review will discuss the potential for manipulating recipient Tregs in vivo prior to and after HSCT (fusion proteins, mAbs). Strategies that would circumvent donor/recipient peripheral blood harvest, cell culture and ex-vivo Treg expansion will be considered for the translational application of Tregs to improve HSCT outcomes.